A longitudinal analysis of conspiracy beliefs and Covid-19 health responses - van Prooijen, Jan-Willem; Amodio, David M; Boot, Arnout; Eerland, Anita; Etienne, Tom; Krouwel, André P M; Onderco, Michal; Verkoeijen, Peter; Zwaan, Rolf A (Psychological medicine, 2023)
BACKGROUND: Little is known about how conspiracy beliefs and health responses are interrelated over time during the course of the coronavirus disease 2019 (Covid-19) pandemic. This longitudinal study tested two contrasting, but not mutually exclusive, hypotheses through cross-lagged modeling. First, based on the consequential nature of conspiracy beliefs, we hypothesize that conspiracy beliefs predict an increase in detrimental health responses over time. Second, as people may rationalize their behavior through conspiracy beliefs, we hypothesize that detrimental health responses predict increased conspiracy beliefs over time. METHODS: We measured conspiracy beliefs and several health-related responses (i.e. physical distancing, support for lockdown policy, and the perception of the coronavirus as dangerous) at three phases of the pandemic in the Netherlands (N = 4913): During the first lockdown (Wave 1: April 2020), after the first lockdown (Wave 2: June 2020), and during the second lockdown (Wave 3: December 2020). RESULTS: For physical distancing and perceived danger, the overall cross-lagged effects supported both hypotheses, although the standardized effects were larger for the effects of conspiracy beliefs on these health responses than vice versa. The within-person change results only supported an effect of conspiracy beliefs on these health responses, depending on the phase of the pandemic. Furthermore, an overall cross-lagged effect of conspiracy beliefs on reduced support for lockdown policy emerged from Wave 2 to 3. CONCLUSIONS: The results provide stronger support for the hypothesis that conspiracy beliefs predict health responses over time than for the hypothesis that health responses predict conspiracy beliefs over time.
Keywords: longitudinální studie; Conspiracy theories; Communicable Disease Control; Longitudinal Studies; lidé; Physical Distancing; longitudinal design; Nizozemsko; Netherlands; health-related beliefs; kontrola infekčních nemocí; fyzický odstup; COVID-19; physical distancing; SARS-CoV2; Humans